Balancing Fidelity with Flexibility and Fit: What do we Really Know about Fidelity of Implementation in Schools?. (April 2013) - Harn, Beth; Parisi, Danielle; Stoolmiller, Mike
Treatment fidelity, or the application of an intervention as it is designed, is a critical issue for the successful implementation of evidence-based practices. Typically it is assumed that evidence-based practices implemented with high fidelity will result in improved outcomes, whereas low fidelity will lead to poorer outcomes. These assumptions presume agreement across researchers and practitioners on what fidelity is, how to measure it, and what level of fidelity optimizes outcomes; however, there is no widespread agreement on any of these issues. This article discusses the dimensions and nuances of treatment fidelity as well as the implications for measuring and analyzing it in relation to student outcomes. The authors review research demonstrating the differential relationship of fidelity across schools, program type, and impact on student outcomes that special educators should consider when designing intervention studies and implementing evidence-based practices. Special educators should prioritize practices and programs with clearly identified components that are empirically validated yet designed flexibly to match various contexts and student populations. Suggestions to support schools in implementing and sustaining evidence-based practices are provided.